2019
DOI: 10.31842/jurnal-inobis.v3i1.121
|View full text |Cite
|
Sign up to set email alerts
|

Building Framework of Work Engagement Social Welfare Institution in Gayo Lues Atjeh

Abstract: This study aims to examine and analyze the influence of Organizational Culture, Job Insecurity, Organizational Commitment, Psychological Meaningfulness Towards Work Engagement in Social Welfare Institutions (LKS) of Central Aceh District, Takengon and Gayo Lues. The research in done through the distribution of questionnaires, and the population of this research is consisted of the employees in the Central Aceh Regency Social Welfare Institution (LKS), Takengon and Gayo Lues. That was done to 50 respondents usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…The next thing discussed in this study is the positive influence exerted by social capital within a group to knowledge in the FSI sector. Good cohesiveness and integration within the organization increase the quality and quantity of work produced based on qualified knowledge possessed by the organization (Nugrahati et al, 2019). The network that is formed in an organization encourages organizational groups to develop more extensive knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The next thing discussed in this study is the positive influence exerted by social capital within a group to knowledge in the FSI sector. Good cohesiveness and integration within the organization increase the quality and quantity of work produced based on qualified knowledge possessed by the organization (Nugrahati et al, 2019). The network that is formed in an organization encourages organizational groups to develop more extensive knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In Wirnipin's research, Nugrahati et al (2019), the results showed that the test results with descriptive statistics resulted in the presentation of the SPSs output. That the influence of Organizational Commitment has a positive and significant effect on organizational performance is accepted.…”
Section: The Role Of Organizational Commitment In Mediating the Influ...mentioning
confidence: 99%
“…Several factors have triggered the inadequate performance of non-profit organizations, one of which is the functioning of the Children Welfare Institutions (LKSA) (Nugrahati et al, 2019;Soelton et al, 2020). The relational, organizational performance of how the performance process can be implemented is why organizational performance cannot be separated from factors that can affect performance, including technology, quality of input, quality of the physical environment, organizational culture, human resource management, which includes aspects of compensation, imbalance, promotions, and others (Soelton et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that as a teacher, it is necessary to have confidence in the ability to think creatively to deal with all problems. Because the level of self-confidence will have an impact on mental health, physical health, work performance, and turnover (Nugrahati et al, 2019). Thus, creative self-efficacy is considered as an important indicator that must be possessed by teachers to achieve work goals and learning objectives.…”
Section: Jp (Jurnalmentioning
confidence: 99%